The numerous approaches to tracking extratropical cyclones and the challenges they present. (20th November 2020) - Walker, Erin; Mitchell, Daniel; Seviour, William
Abstract : The paths taken by extratropical cyclones are key in determining their impacts. However, there is not one single approach or definition of how to locate and track a cyclone. Having multiple methods to track cyclones produces large variations in results, sometimes with contradicting conclusions. For that reason, there is a need to compare storm‐tracking methods to understand further the differences in cyclone trends and their associated impacts.